2022
DOI: 10.3389/fgene.2022.878806
|View full text |Cite
|
Sign up to set email alerts
|

Long-Read Sequencing Revealed Extragenic and Intragenic Duplications of Exons 56–61 in DMD in an Asymptomatic Male and a DMD Patient

Abstract: Expanded carrier screening (ECS) has become an increasingly common technique to assess the genetic risks of individuals in the prenatal or preconception period. Unexpected variants unrelated to referral are being increasingly detected in asymptomatic individuals through ECS. In this study, we reported an asymptomatic male with duplication of exons 56–61 in the DMD gene through ECS using whole-exome sequencing (WES), which was also detected in a male patient diagnosed with typical Duchenne muscular dystrophy (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The instability of the DMD gene structure can be mediated by various factors present around the breakpoints, such as long motifs, nonconsensus microhomologies, low-copy repeats, palindromic sequences, and microindels [18]. Consistent with a previous study [9], recurrent repeat sequences, such as SINE, LINE, and LTR, were observed around most of the breakpoints in the cases analyzed. These ndings provide further support for the mechanistic hypothesis of MMRDR proposed in previous research.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The instability of the DMD gene structure can be mediated by various factors present around the breakpoints, such as long motifs, nonconsensus microhomologies, low-copy repeats, palindromic sequences, and microindels [18]. Consistent with a previous study [9], recurrent repeat sequences, such as SINE, LINE, and LTR, were observed around most of the breakpoints in the cases analyzed. These ndings provide further support for the mechanistic hypothesis of MMRDR proposed in previous research.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported recently, that cases with exonic duplications of DMD gene were accidentally found in the screening project, and eventually were proved to be benign variants. Bai Y et al [9] reported that in the carrier screening program, a normal male was found to carry DMD exons 56-61 duplications, without DMD/BMD-related phenotype. The exonic duplications were con rmed to be external duplications of the DMD gene by LRS and did not affect the normal DMD gene structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of these cases, the extra copy is located within the DMD gene, resulting in disruption of its function; thus, exon duplication in the DMD gene is usually pathogenic [ 15 ]. However, the location of the duplication breakpoints differs among affected families; therefore, the same duplication may be pathogenic in one family but benign in another [ 16 , 17 ]. In a previous study, fluorescent multiplex qPCR and MLPA identified three non-contiguous duplications of exons 44–48, 51–59, and 64–79 in a patient with DMD, which were classified as pathogenic [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luce et al [ 19 ] used a multi-technique algorithm, including MLPA, microarrays, and next-generation whole-genome sequencing for the molecular characterization of complex structural variants in the DMD gene. Recently, long-read sequencing and Sanger sequencing revealed that the duplication of exons 56–61 in the DMD gene was a tandem repeat in a patient with DMD and that duplication occurred outside the DMD gene in an asymptomatic male [ 16 ]. We used long-read sequencing and breakpoint analysis to illustrate the molecular characteristics of three non-contiguous DMD duplications, which proved to be benign.…”
Section: Discussionmentioning
confidence: 99%